Wien Bridge oscillator as a suitable power source for the wireless charge of biomedical devices under an inductive power transfer system. - Adam, Abdul-Wahab A.; Hashim, Khalil I.; khazmi, Yousef O. (Libyan Journal of Science &Technology, 2025)
An inductive power transfer (IPT) system is a mechanism used to solve charging problems to connect with wires for devices that are difficult, such as stimulation devices implanted inside the human body for the heart and nervous system, also for commercial devices such as charging mobile phones. In this paper, we studied the oscillator of the Wien bridge and how to set it in practice as a source of power for the wireless IPT system, in terms of the output and the permissible frequency range, we also studied the oscillator theory and the effect of physical parameters such as the values ​​of resistors and capacitors on the frequency, voltage, current, power, and the form of the resulting wave. By running a simulation via NI MULTISIM 14.2, a program specialized in electronic circuits, we found that the Wien bridge oscillator with LM7171AIM operational amplifier ​​has a noise-free sine wave shape, with well frequency stability. In addition, it has a low power that can be controlled through the bridge as required by the target devices, and it has a low-frequency range that satisfies the safety standards. In principle, this makes it very convenient as a power source for biomedical devices implanted inside the human body.